RmmLII, a novel marine-derived N-acyl homoserine lactonase from Tritonibacter mobilis - Shen, Yu; Liu, Dongwei; Yue, Xiaoxue; Wang, Dongliang; Wang, Zhikui; Wang, Xu; Liu, Gang; Liu, Xiaodong; Cai, Xiulei (Frontiers in Microbiology, 2025)
IntroductionQuorum sensing (QS) is a bacterial intercellular communication system that can regulate the expression of various virulence genes coordinate the group behaviors of the bacteria by sensing the concentration of signaling molecules in the surrounding environment. An increase in bacterial drug-resistance has been caused by the widespread use of antibiotics, making it urgent to identify safe and effective alternatives to antibiotics. Quorum quenching (QQ) is a strategy to control bacterial infections by disrupting the QS system, which reduces pathogenicity or increases biofilm susceptibility to antibiotics. Several natural agents with QQ activity have been identified, including small molecular inhibitors and QQ enzymes that disrupt bacterial QS by degrading or modifying the QS signal molecules.MethodsIn the present study, We performed heterologous recombinant expression of the potential QQ enzyme-encoding gene RmmLII from Tritonibacter mobilis YJ3. The degradation activity of RmmLII against AHLs was assessed in vitro using the A136 liquid X-Gal assay and a plate detection method. Furthermore, the degradation mechanism of RmmLII was analyzed via high-performance liquid chromatography-mass spectrometry (HPLC-MS). The effects of RmmLII on extracellular proteases production, pyocyanin synthesis, rhamnolipids secretion, biofilm formation, and motility of Pseudomonas aeruginosa PAO1 were evaluated in vitro. Additionally, a mouse infection model was established using P. aeruginosa PAO1 to investigate the impact of RmmLII on the production of inflammatory cytokines IL-1β, IL-6, and TNF-α, as well as mouse survival rates.ResultsA novel N-acylhomoserine (AHL) lactonase RmmLII was identified and characterized from T. mobilis YJ3, which was isolated from healthy shrimp in our previous work. Through amino acid sequence alignment, a conserved “HXHXDH” domain was detected in RmmLII, indicating that RmmLII belongs to the phosphotriesterase (PTE) family. Recombinant RmmLII could effectively degrade AHLs in vitro, both long-chain and short-chain AHLs, ranging from C6 to C14. It exhibited the strongest quenching effect on C6-HSL, C8-HSL, C10-HSL, 3-oxo-C8-HSL, 3-oxo-C10-HSL, 3-oxo-C12-HSL, and 3-oxo-C14-HSL, while the quenching effect on C14-HSL and 3-oxo-C6-HSL was relatively weaker, especially with more notable degradation activity towards long-chain AHLs with a substitution of oxo-group at the C-3 position. HPLC-MS analysis revealed that RmmLII could hydrolyze the ester bond of AHLs. In addition, RmmLII significantly inhibited the production of extracellular proteases, pyocyanin, rhamnolipids, biofilm formation, as well as motility of P. aeruginosa PAO1 in vitro. It also reduced the production of inflammatory factors IL-1β, IL-6, and TNF-α, thereby improving the survival rates of mice infected with PAO1 in vivo.DiscussionThis study demonstrates the potential application of RmmLII in controlling PAO1 infections, offering new insights for the development of novel antibiotic alternatives. RmmLII has the potential as a therapeutic agent for application in the mitigating PAO1 infections.